Farmers' pesticide usage practices in the malaria endemic region of North-Western Tanzania: implications to the control of malaria vectors - Anitha Philbert; Sylvester Leonard Lyantagaye; Gamba Nkwengulila (BMC, 2019)
Abstract Background Pesticides remain the mainstay for the control of agricultural pests and disease vectors. However, their indiscriminate use in agriculture has led to development of resistance to both crop pests and disease vectors. This threatens to undermine the success gained through the implementation of chemical based vector control programs. We investigated the practices of farmers with regard to pesticide usage in the vegetable growing areas and their impact on susceptibility status of An. gambiae s.l. Methods A stratified multistage sampling technique using the administrative structure of the Tanzanian districts as sampling frame was used. Wards, villages and then participants with farms where pesticides are applied were purposively recruited at different stages of the process, 100 participants were enrolled in the study. The same villages were used for mosquito larvae sampling from the farms and the surveys were complimented by the entomological study. Larvae were reared in the insectary and the emerging 2-3 days old female adults of Anopheles gambiae s.l were subjected to susceptibility test. Results Forty eight pesticides of different formulations were used for control of crop and Livestock pests. Pyrethroids were the mostly used class of pesticides (50%) while organophosphates and carbamates were of secondary importance. Over 80% of all farmers applied pesticides in mixed form. Susceptibility test results confirmed high phenotypic resistance among An. gambiae populations against DDT and the pyrethroids (Permethrin-0.75%, Cyfluthrin-0.15%, Deltametrin-0.05% and Lambdacyhalothrin-0.05%) with mortality rates 54, 61, 76 and 71%, respectively. Molecular analysis showed An. arabiensis as a dominant species (86%) while An. gambiae s.s constituted only 6%. The kdr genes were not detected in all of the specimens that survived insecticide exposures. Conclusion The study found out that there is a common use of pyrethroids in farms, Livestocks as well as in public health. The study also reports high phenotypic resistance among An. gambiae s.l against most of the pyrethroids tested. The preponderance of pyrethroids in agriculture is of public health concern because this is the class of insecticides widely used in vector control programs and this calls for combined integrated pest and vector management (IPVM).